PENGARUH KOMITMEN KARYAWAN, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PERUMDA AIR MINUM TIRTA RANDIK MUSI BANYUASIN - Meila Piura; Muhammad Wadud (JIEM : Journal Of International Entrepreneurship And Management, 2026)
This study examines the influence of employee commitment, work discipline, and work motivation on employee performance at PERUMDA Air Minum Tirta Randik Musi Banyuasin. A quantitative approach with a causal associative design was employed. The population consisted of 382 employees, and 195 respondents were selected using proportionate stratified random sampling. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 25. The findings reveal that employee commitment, work discip line, and work motivation each have a positive and significant effect on employee performance. Simultaneously, the three variables also significantly influence employee performance, with a coefficient of determination (R²) of 0.689, indicating that 68.9% of the variation in employee performance is explained by the proposed model. Employee commitment emerged as the most dominant variable affecting performance. Therefore, strengthen ing employee commitment, supported by improved work discipline and motivation, is essential to enhance employee performance and organizational service quality.